Mothers’ Trajectories of Depressive Symptoms Across Mexican-Origin Adolescent Daughters’ Transition to Parenthood - Updegraff, Kimberly A. (2013)
This study draws from a life-course perspective in examining trajectories of mothers’ depressive symptoms across their adolescent daughters’ adjustment to parenthood in 204 Mexican-origin families using latent class growth analysis. Four distinct trajectories were identified based on mothers’ depressive symptoms prior to the birth and 10 and 24 months postpartum. Two trajectories were characterized by stable levels of depressive symptoms but were differentiated in their levels of symptoms (i.e., High/Stable and Low/Stable). The remaining two trajectories were characterized by changes from pre- to post-birth, with one group exhibiting increases in depressive symptoms (i.e., Low/Post-Birth Increase) and the other group characterized by decreases in depressive symptoms (i.e., Low/Post-Birth Decrease). Consistent with a risk and resilience perspective, mothers with more disadvantaged socioeconomic circumstances and fewer intrapersonal resources (i.e., self-esteem, ethnic identity affirmation) were more likely to be members of the High/Stable group. In addition, daughters of mothers in the High/Stable group were more likely to have lower self-esteem as compared to daughters in the other three groups. Collectively, these findings suggested that the High/Stable group was at risk for adjustment difficulties from the third trimester to two years postpartum. In contrast, membership in the Low/Post-Birth Decrease trajectory group was associated with lower depressive symptoms and higher self-esteem for mothers and daughters. Findings point to the need to identify mothers who are at risk for depressive symptoms during their adolescent daughters’ pregnancy and offer prevention and intervention programs that reduce risks and enhance protective factors.